An ESIPT‐Dependent AIE Fluorophore Based on HBT Derivative: Substituent Positional Impact on Aggregated Luminescence and its Application for Hydrogen Peroxide Detection. Issue 5 (18th December 2021) - Zeng, Guanling; Liang, Zhenhao; Jiang, Xiao; Quan, Tingting; Chen, Tongsheng
Abstract: Aiming to develop the facile organic fluorophore possessing excited state intramolecular proton transfer (ESIPT) and aggregation‐induced emission (AIE), we designed and synthesized two isomers with different linkage site between hydroxyl of 2‐(2‐hydroxyphenyl) benzothiazole (HBT) and a benzothiazole substituent (para position refers to p‐ BHBT and ortho position refers to o‐ BHBT). Fluorescence emission properties of p‐ BHBT and o‐ BHBT in THF/water mixtures with different water volume fractions indicated an opposite luminescence in aggregates, in which p‐ BHBT showed an ESIPT‐dependent AIE properties while o‐ BHBT displayed ESIPT effect and aggregation‐caused quenching (ACQ) qualities. A possible mechanism for molecular actions to illustrate the aggregating luminescence alteration of these two isomers had been proposed and verified by theoretical and experimental studies. More importantly, Probe‐1, generated from dual ESIPT‐AIE fluorophore p‐ BHBT, was successfully used as a ratiometric fluorescent chemosensor for highly selective (above 15‐fold over other ROS) and sensitive (69‐fold fluorescence enhancement with 0.22 μM of detection limit) detection of hydrogen peroxide in aqueous solution and living cells, respectively. Abstract : Two positional isomers are presented, p ‐BHBT and o‐BHBT, and their structural feature is mainly different in one BT substituent position on HBT fluorophore. Surprisingly, they exhibited totally opposite luminescence behaviour in water/THF cosolvents with different water volume fractions (fw). More importantly, the unique AIE‐ESIPT properties allowed p ‐BHBT to construct the chemosensor, Probe‐1, for highly selective and sensitive detection of hydrogen peroxide in aqueous solution and living cells, respectively.